Can Increased Urotensin II Levels Predict COVID-19 Severity? - Telo, Selda; Kuluöztürk, Mutlu (My University, 2023)
Objective: It is aimed to determine the urotensin II (UII) level and prognostic value in patients diagnosed with COVID. Materials and Methods: Ninety consecutive patients with COVID-19 diagnosis and 30 healthy individuals were evaluated. COVID-19 patients were classified as mild-moderate and severe patients upon admission. Complete blood cell counts, serum UII and CRP levels were determined before the treatment. Hospital mortality, transfer to intensive care unit (ICU) and discharged patients were recorded. Results: It was determined that 76 patients (84.4%) were discharged while 14 patients (15.6%) were transferred to ICU or died. Increased mortality and transfer to the ICU rates were found in severe COVID-19 patients than the mild-moderate COVID-19 patients. Serum UII levels were statistically significantly increased in severe COVID-19 patients than mild-moderate COVID-19 patients and healthy controls. Also, mild-moderate COVID-19 patients had increased levels of UII than the healthy controls. Increased UII levels were found in COVID-19 patients who were transferred to ICU or exitus compared to discharged COVID-19 patients. When the cut-off value of UII was taken as ?5.26 by ROC analysis for the predicting of severity of disease, UII had an area under the curve (AUC) in the ROC curve of 0.688 (0.580-0.796; 95% CI; p<0.01). Also, UII had a sensitivity of 80% and specificity of 59%. Conclusion: Our results demonstrated that increased levels of UII may be related to disease severity in COVID-19 patients. Initial evaluation of UII in these patients can help predict the adverse outcomes.
Keywords: Tıbbi Araştırmalar Deneysel; Solunum Sistemi; Yoğun Bakım; Tıp